The secret life of the grown-up brain : the surprising talents of the middle-aged mind - Strauch, Barbara (New York : Penguin Books, 2010)
In her impeccably researched book, science writer Barbara Strauch explores the latest findings that demonstrate, through the use of technology such as brain scans, that the middle-aged brain is more flexible and more capable than previously thought. By detailing exactly the normal, healthy brain functions over time, Strauch also explains how its optimal processes can be maintained.
Includes bibliographical references and index.
Keywords: Middle-aged persons -- Mental health; Memory disorders; Brain